On the zeros of a class of generalized hypergeometric polynomials - Bracciali, Cleonice Fátima [UNESP]; Moreno-Balcazar, Juan José (Elsevier B.V., 2015)
We obtain the asymptotic behavior of the zeros of a class of generalized hypergeometric polynomials. For this purpose, we make use of a Mehler-Heine type formula for these polynomials. We illustrate these results with numerical experiments and some figures.
Keywords: Generalized hypergeometric polynomials; Asymptotics; Zeros